Combining deficit irrigation and nutrient amendment enhances the water productivity of tomato (Solanum lycopersicum L.) in the tropics - Amankwaa-Yeboah, Patricia; Aruna Akoriko, Fati; Amponsah, William; Yeboah, Stephen; Brempong, Mavis Badu; Keteku, Agbesi K. (Frontiers in Sustainable Food Systems, 2023)
Water availability for irrigation farming is one of the greatest challenges associated with the increasing spatio-temporal effects of climate change and variability on tomato production, especially in tropical regions. This study was conducted to demonstrate the combined effect of irrigation and nutrient management as a water-saving strategy to maximize nutrient and water productivity in tomato production. The research was conducted in a screen house at the CSIR-Crops Research Institute (CSIR-CRI), Kumasi, Ghana using the split-plot design in the 2020 and 2021 cropping seasons. The main plot consisted of a single full irrigation at 100% recommended crop water requirement and two deficit irrigation levels (75 and 50% of the crop water requirement). The subplots consisted of two nutrient amendments (inorganic fertilizer and organic compost) and a control (without any nutrient amendment). Data from the research was used to parameterize the DSSAT CCROPGRO model to simulate the interactive effect of irrigation and nutrient management on the yield of tomatoes. Plant height and stem girth did not have a specific influence on tomato yield, but the number of branches had a positive effect on tomato yield. The combined use of inorganic fertilizer and full irrigation was found to improve tomato yield up to 7691.4 and 9009.9 kg/ha whereas treatment with no fertilizer application at 50% deficit irrigation recorded the lowest tomato yield of 1423.9 and 1739.2 kg/ha in 2020 and 2021, respectively. For the two deficit irrigations (50 and 75% ETc), organic compost produced the highest tomato yield. Deficit irrigation recorded higher crop water productivity (CWP) compared to full irrigation. At 50% deficit irrigation, organic compost recorded the highest CWP of 4.54 kg/m3 in 2020 while inorganic fertilizer recorded the highest CWP of 5.52 kg/m3 in 2021. No fertilizer at full irrigation recorded the lowest CWP of 1.37 and 1.67 kg/m3 in 2020 and 2021, respectively. This study has revealed that deficit irrigation with organic compost has the same effect on yield and water productivity as full irrigation with inorganic fertilizer. The strong agreement observed between the measured and simulated yields under the different irrigation and nutrient management shows that the DSSAT CROPGRO tomato model can be used to simulate tomato fruit yield under future climate scenarios. However, the general overestimation of the measured tomato yield shows the limitations of the model to simulate the real-world complexity of cropping systems under controlled conditions. This calls for more research into crop system modeling in controlled environment agriculture.